Ethical considerations in sarcopenia research - Gita Shafiee; Narges Zargar Balajam; Ramin Heshmat; Bagher Larijani (Journal of Medical Ethics and History of Medicine, 2023)
As the population ages, the number of older people with various geriatric diseases is increasing.  Sarcopenia is one of the important geriatric diseases with high mortality and morbidity. Some research needs to understand risk factors, diagnosis, and prevention, and develop treatment options with high safety and efficacy for sarcopenic people. To reduce the risks involved with sarcopenic people in clinical research, it is necessary to consider the ethical review of research on this issue. Therefore, this study aimed to guide on the ethical issues of sarcopenia research.